National Partnership for Maternal Safety Recommended Maternal Early Warning Criteria Are Associated With Maternal Morbidity. Issue 2 (June 2020) - Arnolds, D.E.; Smith, A.; Banayan, J.M.; Holt, R.; Scavone, B.M.
Abstract : ( Anesth Analg . 2019;129:1621–1626) Maternal mortality and severe obstetric morbidity in the United States are increasing by substantial rates. From 1987 to 2010, mortality increased to near 75%, and severe morbidity increased by a similar rate. Many maternal deaths are due to a delayed response to clinical warning signs. It is estimated close to half of maternal deaths attributed to provider factors are preventable. Therefore, vital sign (VS) triggers were proposed as components of early warning systems in the obstetric population. The maternal early warning criteria (MEWC) were created by The National Partnership for Maternal Safety (NPMS) to identify pregnant women at risk for morbidity and mortality. It is a single parameter system in which triggering any criterion prompts bedside evaluation. The goal of this study was to evaluate the relationship between the MEWC and subsequent maternal morbidity and mortality